FUNGSI TINDAK TUTUR DIREKTIF PERINTAH DALAM PERCAKAPAN MAHASISWA PPL DENGAN SISWA SMP LABOR PADA APLIKASI GRUP TELEGRAM SMP LABOR BULAN SEPTEMBER 2021 (KAJIAN PRAGMATIK) - Ade Rahima; Yulisah Yulisah (Universitas Batanghari, 2022)
The directive speech act function in the conversation of PPL Students is often used. Directive utterances found, such as commanding, asking, solicitation, prohibition, advice, and questions. Therefore, this research aims to describe the function of command directive speech acts in conversations between PPL students and SMP Labor students on the telegram application of the SMP Labor group 15 – 28 September 2021 (a pragmatic study). The research method used is descriptive quantitative, and data collection techniques are carried out using screenshot techniques. The data in this study is in the form of utterances spoken by PPL students with SMP Labor students on the school’s group telegram application. Data in the form of speech that is included in the directive speech act. The data were analyzed using pragmatic analysis techniques. Based on the analysis results, it can be concluded that there is one data related to the function. The functions of directive speech acts are commands, requests, prohibitions, advice, and questions.